La condición del campesinado navarro-aragonés entre los siglos IX y XII: una revisión crítica. The peasant condition in Navarre and Aragon between the 9th and 12th centuries: a critical assessment - Larrea, Juan José (En la España Medieval, 2006)
The social history of peasantry in Navarre and Aragon entered a new stage twenty years ago. Since then some basic questions have been settled, including the well-established generalized serfdom during the second and first halves of the 11th and 12th centuries, respectively. In contrast, other matters remain controversial: the origins of the serfdom and the mechanisms by which it expanded and evolved. From a critical and personal perspective, this paper focuses on the main studies on the subject, the agreements, disagreements and methodological problems. New trends in this field are summarized and new directions are also proposed.